Icy Moon Penetrator Organic Analyzer Post-Impact Component Analysis - Govinda Raj, Chinmayee; Cato, Michael; Speller, Nicholas Colby; Duca, Zachary; Putman, Philip; Epperson, Jason; Foreman, Shaun; Kim, Jungkyu; Stockton, Amanda (Frontiers in Astronomy and Space Sciences, 2022)
Europa is an established high-priority astrobiology target where identifying chemical signatures of life is one of NASA's highest-priority goals. Remote sensing techniques are powerful tools for extraterrestrial exploration, but in situ data through analyses of subsurface materials is necessary for ground-truthing these habitability investigations. Instrument designs fitting small volume, mass, and power consumption envelopes have a high potential for enabling efficient, low-cost missions. The Ice Shell Impact Penetrator (IceShIP) is a state-of-the-art miniaturized payload design dedicated to lower-cost extraterrestrial impact-penetrator missions. It houses the Icy Moon Penetrator Organic Analyzer (IMPOA), a first-of-its-kind payload housing miniaturized analytical instrumentation employing laser-induced fluorescence for the detection of low concentration organic species pervasive in the solar system. IMPOA is capable of sustaining high g-loads, avoiding the need for soft landing platforms, and facilitating crustal penetration for subsurface sample analyses. Three IMPOA test articles with varying material choices, construction designs, and internal components were modeled using COMSOL Multiphysics and then tested at 12 k-g, 25 k-g, and 50 k-g accelerations in an air gun assembly. The internal components consisted of linear piezoelectric micro-actuators, microcontroller board, mock microfluidic glass wafers, collimating lens, optical filters, and laser diodes. This work focuses on an extensive analysis of the impact-tested components. All components physically survived the impact tests except the mock microfluidic disk. Functionality tests of the individual components confirm their survival post-impact. All components used in this design are commercially available or easily machinable, which will simplify technology transfer for further technology elevation. Impact-resistance, miniaturization, energy efficiency, and cost-effectiveness are pivotal for impact-penetrator space-flight missions. This work satisfies these key aspects and demonstrates technology of a novel design for astrobiological in situ instrumentation.